Pedagogi Kritis dan Pembelajaran Bahasa Asing: Sebuah Ancangan Awal - Damanhuri, Damanhuri (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2015)
AbstractThis article is a prelimenary research on the main trends in our contemporary pratices of foreign language learning (especially Arabic and English). It tries to investigate that “pedagogy of mainstream”—to borrow A. Suresh Canagarajah’s phrase—interogate it, propose “critical pedagogy” as its alternative approach as well as explain—what so-called—aspects of metalinguistics of human language and, in final analysis, pay attention tothe possibility to incorporate them in the practices of foreign language learning. Key Words:Pembelajaran bahasa asing, pedagogi arus utama/pedagogi kritis, metalinguistik